Nutrient Deficiencies and Potential Alteration in Plasma Levels of Naturally Acquired Malaria-Specific Antibody Responses in Tanzanian Children - Mbugi, Erasto V.; Hartog, Gerco den; Veenemans, Jacobien; Chilongola, Jaffu O.; Verhoef, Hans; Savelkoul, Huub F. J. (Frontiers in Nutrition, 2022)
Immunoglobulin G (IgG) subclasses have been signaled to confer naturally acquired immunity to Plasmodium falciparum malaria. Cytophilic IgG1 and IgG3 by their potential for opsonization, phagocytosis and antibody-dependent cellular inhibition in association with monocytes have been suggestive for the critical role in malaria. The potential for production of antibodies is influenced by micronutrient status. This study aimed at exploring the effect of micronutrients, particularly zinc status on the profiles of IgG subclasses in 304 Tanzania children aged ≤ 5 years. An enzyme-linked immunosorbent assay was performed using whole asexual blood stage malaria antigens to determine plasma malaria-specific antibody titres. This study was done in the years from 2005 – 2010. Plasma concentrations of zinc and magnesium were measured by inductively-coupled plasma atomic emission spectrometry and results correlated with plasma IgG subclasses levels. The findings reveal zinc deficiency to possibly influence the production of IgM, total IgG and several IgG subclasses in a malaria status-dependent manner. Among IgG subclasses, IgG3 and partly IgG2 displayed remarkable changes in the zinc deficient children with IgG3 predominating in subjects with malaria. Zinc, magnesium, iron deficiency anaemia and malaria status did not influence the association between IgG3 and IgG4. Under conditions of micronutrient deficiency and malaria status, an imbalance in IgG subclasses production may occur resulting into predominantly higher levels of IgG3 and IgG2 that may not confer sufficient protection. The profile of both cytophilic and non cytophilic IgG subclasses have shown to be variably influenced by zinc status, the effects that vary with age at least in under-fives. These results provide an insight for inclusion of micronutrients, particularly precise amounts of zinc in future malaria interventional programs in endemic areas.